2019
DOI: 10.1016/s1569-9056(19)33774-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical factors affecting semen improvement after microsurgical subinguinal varicocelectomy: Which subfertile patients benefit from surgery?

Abstract: Background: The exact mechanism of varicocele-related infertility is still elusive, therefore, the current challenges for its management lie in determining which patients stand to benefit most from surgical correction. The authors aimed to assess the clinical factors affecting semen improvement after left microsurgical subinguinal varicocelectomy (MSV) in relation to patient age, ultrasound varicocele grading (USVG), and presence of a right subclinical varicocele (RSV). Methods: From 2010 to 2017 a total of 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Despite the detrimental effects of varicocele on male fertility, varicocele repair effect on fertility remains debatable (Yetkin & Ozturk, 2018). However, most of the studies reported that varicocele repair resulted in improvement in semen parameters (Gomaa et al., 2018; Palmisano et al., 2019). Palmisano et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the detrimental effects of varicocele on male fertility, varicocele repair effect on fertility remains debatable (Yetkin & Ozturk, 2018). However, most of the studies reported that varicocele repair resulted in improvement in semen parameters (Gomaa et al., 2018; Palmisano et al., 2019). Palmisano et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have addressed the mechanism of testosterone/oestradiol (T/E) balance in regulation of testicular and erectile functions (El‐Sakka, 2013; Yamamoto et al., 1995). Sub‐inguinal varicocelectomy has resulted in significant improvement of semen variables and androgen pattern in infertile patients (Gomaa et al., 2018; Palmisano et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…(2014) and Palmisano et al. (2019) show a significant predictive role of this factor. According to Bozhedomov et al.…”
Section: Discussionmentioning
confidence: 87%
“…Our results show that the male age should also be considered a significant factor. The previous studies yielded conflicting results: some researchers considered the male age to be a reliable predictor of improved fertility after varicocelectomy (Kimura et al., 2017; Palmisano et al., 2019; Samplaski et al., 2014), while others argued that this factor did not significantly affect varicocelectomy outcomes (Almekaty et al., 2019; Çayan et al., 2017; Zhang et al., 2017). It follows from our data that male age is a significant factor of fertility recovery after varicocelectomy; however, it may be not independent, but only a co‐factor, the influence of which is manifested depending on the initial semen parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation